Alternative Lengthening of Telomeres: DNA Repair Pathways Converge. Issue 12 (December 2017) - Sobinoff, Alexander P.; Pickett, Hilda A.
Abstract : Telomeres shorten during each cellular division, with cumulative attrition resulting in telomeric damage and replicative senescence. Bypass of replicative senescence precipitates catastrophic telomere shortening or crisis, and is characterized by widespread genomic instability. Activation of a telomere maintenance mechanism (TMM) is necessary to stabilise the genome and establish cellular immortality through the reconstitution of telomere capping function. The alternative lengthening of telomeres (ALT) pathway is a TMM frequently activated in tumors of mesenchymal or neuroepithelial origin. ALT is a homology-directed recombination-dependent replication pathway that utilizes telomeric templates for synthesis; however, its precise protein requirements have remained elusive. Recently, several developments have shed light on the DNA repair pathways that become engaged at ALT telomeres, implicating ALT telomeres as DNA repair hot spots. Here, we review recent discoveries regarding the ALT mechanism, and discuss how DNA repair pathways converge to maintain the length and functional integrity of telomeres in ALT cancers. Trends: Stalled replication fork restart and alternative nonhomologous end joining (alt-NHEJ) repair of telomeric double-strand breaks (DSBs) repress ALT activity. Ineffective repair of spontaneous telomere damage promotes the engagement of homologous recombination (HR) repair pathways. ALT cells extend their telomeres through break-induced telomere synthesis, resulting in long tract telomere extensions of up to 70 kb. ALT-mediated break-induced telomere synthesis can proceed via RAD51-dependent intertelomeric recombination or RAD51-independent intratelomeric recombination. Break-induced telomere synthesis utilizes a noncanonical replisome comprising DNA polymerase δ (Polδ)-PCNA-RFC1 and can be initiated by DNA polymerase η (Polη). The BTR complex initiates POLD3-dependent break-induced telomere synthesis followed by dissolution, with no overall exchange of telomeric DNA. ALT-mediated telomere synthesis is counteracted by the resolution activity of SLX4.